Psoriasis and Psoriasiform Eruptions in Pediatric Patients with Inflammatory Bowel Disease Treated with Anti–Tumor Necrosis Factor Alpha Agents. Issue 3 (17th February 2017) - Eickstaedt, Joshua B.; Killpack, Luke; Tung, Jeanne; Davis, Dawn; Hand, Jennifer L.; Tollefson, Megha M.
Abstract: Background: Anti–tumor necrosis factor alpha (TNF‐α) agents are used to treat a variety of autoimmune and inflammatory conditions, including psoriasis. Paradoxically, numerous reports have documented new‐onset or exacerbation of psoriasis or psoriasiform skin lesions (PSO) in patients treated with these agents for conditions other than PSO—particularly in adults with inflammatory bowel disease (IBD). Not much is known regarding similar cases in children. Methods: A retrospective chart review was performed on children younger than 19 years of age with IBD seen at the Mayo Clinic between 2003 and 2015 who developed new‐onset or recurrent PSO while undergoing anti‐TNF‐α therapy. Results: Fourteen children developed PSO while undergoing anti‐TNF‐α therapy for IBD. All three anti‐TNF‐α agents (infliximab, adalimumab, certolizumab) used to treat IBD in this series led to induction or recurrence of PSO lesions. The median time to development of PSO was 11 months (range 0–48 mos), the median age was 15 years (range 12.5–17.5 yrs), and 57% of patients were male. IBD activity was quiescent in 93% of cases at PSO onset. Seven patients (50%) discontinued their initial anti‐TNF‐α therapy because of their skin disease. Ultimately, four patients (29%) had to discontinue all anti‐TNF‐α therapy to induce PSO resolution. Conclusion: TNF‐α antagonist–induced PSO in children with IBD is a rarely reported adverse reaction. PSO onset has a variable latency, but usually occurs during IBD remission, with a slight male bias. Nearly half of patients required a change in their initial anti‐TNF‐α agent despite conventional skin‐directed therapies, and one‐third of patients discontinued all anti‐TNF‐α therapy because of PSO.